Crisis education and service program designs : a guide for administrators, educators, and clinical trainers - Hoff, Miracle; Hoff, Lee Ann.; Hoff, Lee Ann. (2012)
'Crisis Education and Service Program Designs, 2nd ed, is a guide to educators, administrators, and clinical trainers who may otherwise feel ill-prepared to teach crisis theory and practice. It provides a framework for more systematic inclusion of crisis content (e.g. critical life events, violence, victimization, suicide and psychiatric emergencies) in the formal preparation of health and human service professionals. Further, it offers criteria for developing programs and practice protocols that balance attention to the psychosocial and biomedical needs of people in distress and crisis. By clearly delineating what crisis care is and is not, the revised Crisis Education and Service Program Designs shows that this facet of mental health care is neither a mere'band-aid' (as previously thought) nor a panacea for what ails the healthcare system. Instead, it is an essential element of the total health-service delivery system that recognizes the whole human being, not only his or her medical or psychiatric diagnosis. Readers will find that this book fills the current gaps in knowledge and training; contributes to a more holistic practice by all human service professionals; and shows educators and practitioners how to adopt a nondual approach to working with trauma survivors' minds and bodies'--Provided by publisher.
Rev. ed. of: Creating excellence in crisis care / Lee Ann Hoff, Kazimiera Adamowski. 1st ed. c1998.
Includes bibliographical references and index.
Keywords: Crisis intervention (Mental health services) -- Study and teaching; Crisis intervention (Mental health services) -- Study and teaching